HIF1α-BNIP3-mediated mitophagy protects against renal fibrosis by decreasing ROS and inhibiting activation of the NLRP3 inflammasome - Jialin Li; Qisheng Lin; Xinghua Shao; Shu Li; Xuying Zhu; Jingkui Wu; Shan Mou; Leyi Gu; Qin Wang; Minfang Zhang; Kaiqi Zhang; Jiayue Lu; et al. (Cell Death and Disease, 2023)
Abstract Chronic kidney disease affects approximately 14.3% of people worldwide. Tubulointerstitial fibrosis is the final stage of almost all progressive CKD. To date, the pathogenesis of renal fibrosis remains unclear, and there is a lack of effective treatments, leading to renal replacement therapy. Mitophagy is a type of selective autophagy that has been recognized as an important way to remove dysfunctional mitochondria and abrogate the excessive accumulation of mitochondrial-derived reactive oxygen species (ROS) to balance the function of cells. However, the role of mitophagy and its regulation in renal fibrosis need further examination. In this study, we showed that mitophagy was induced in renal tubular epithelial cells in renal fibrosis. After silencing BNIP3, mitophagy was abolished in vivo and in vitro, indicating the important effect of the BNIP3-dependent pathway on mitophagy. Furthermore, in unilateral ureteral obstruction (UUO) models and hypoxic conditions, the production of mitochondrial ROS, mitochondrial damage, activation of the NLRP3 inflammasome, and the levels of αSMA and TGFβ1 increased significantly following BNIP3 gene deletion or silencing. Following silencing BNIP3 and pretreatment with mitoTEMPO or MCC950, the protein levels of αSMA and TGFβ1 decreased significantly in HK-2 cells under hypoxic conditions. These findings demonstrated that HIF1α-BNIP3-mediated mitophagy played a protective role against hypoxia-induced renal epithelial cell injury and renal fibrosis by reducing mitochondrial ROS and inhibiting activation of the NLRP3 inflammasome.